Deletion of SNAP-23 Results in Pre-Implantation Embryonic Lethality in Mice - Suh, Young Ho; Yoshimoto-Furusawa, Aki; Weih, Karis A.; Tessarollo, Lino; Roche, Katherine W.; Mackem, Susan; Roche, Paul A. (PLOS ONE, 2011)
SNARE-mediated membrane fusion is a pivotal event for a wide-variety of biological processes. SNAP-25, a neuron-specific SNARE protein, has been well-characterized and mouse embryos lacking Snap25 are viable. However, the phenotype of mice lacking SNAP-23, the ubiquitously expressed SNAP-25 homolog, remains unknown. To reveal the importance of SNAP-23 function in mouse development, we generated Snap23-null mice by homologous recombination. We were unable to obtain newborn SNAP-23-deficient mice, and analysis of pre-implantation embryos from Snap23Δ/wt matings revealed that Snap23-null blastocysts were dying prior to implantation at embryonic day E3.5. Thus these data reveal a critical role for SNAP-23 during embryogenesis.